2012
DOI: 10.1080/10916466.2010.501359
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cavitating Jet Effect on Bitumen Separation from Oil Sands

Abstract: The effect of a submerged cavitating jet on as-mined oil sands is investigated in order to assess the potential of this new technological approach to bitumen extraction at low temperatures. A series of laboratory experiments have been performed using a custom-made experimental apparatus that allowed ablation measurements of oil sands samples and provided information regarding the volume of the extracted bitumen, the remaining volume of cleaned sand, the effects of the water temperature, and the time of exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…When toluene extraction was selected as the reference, the relative increment in the H/C atom ratio and the relative decrement in sulphur and nitrogen content were significant, as shown in Figure S2. This finding may be due to the lower resin and asphaltene content in bitumen samples separated by dissolution‐precipitation compared to those separated by toluene extraction as resins and asphaltenes possess high sulphur and nitrogen content and a low H/C atom ratio . Furthermore, the H/C atom ratio and the sulphur and nitrogen content were related to the choice of precipitating agent, as bitumen separated with methanol as the precipitating agent had the lowest sulphur and nitrogen content and the highest H/C atomic ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When toluene extraction was selected as the reference, the relative increment in the H/C atom ratio and the relative decrement in sulphur and nitrogen content were significant, as shown in Figure S2. This finding may be due to the lower resin and asphaltene content in bitumen samples separated by dissolution‐precipitation compared to those separated by toluene extraction as resins and asphaltenes possess high sulphur and nitrogen content and a low H/C atom ratio . Furthermore, the H/C atom ratio and the sulphur and nitrogen content were related to the choice of precipitating agent, as bitumen separated with methanol as the precipitating agent had the lowest sulphur and nitrogen content and the highest H/C atomic ratio.…”
Section: Resultsmentioning
confidence: 99%
“…This finding may be due to the lower resin and asphaltene content in bitumen samples separated by dissolution-precipitation compared to those separated by toluene extraction as resins and asphaltenes possess high sulphur and nitrogen F I G U R E 4 Chemical group composition and residual carbon value of bitumen separated by the dissolution-precipitation method F I G U R E 5 H/C atom ratio and sulphur and nitrogen contents of bitumen separated by toluene extraction and dissolutionprecipitation content and a low H/C atom ratio. [22,23] Furthermore, the H/C atom ratio and the sulphur and nitrogen content were related to the choice of precipitating agent, as bitumen separated with methanol as the precipitating agent had the lowest sulphur and nitrogen content and the highest H/C atomic ratio. Hence, methanol showed the best bitumen processing performance.…”
Section: Component Analysis Of Separated Bitumenmentioning
confidence: 99%
“…One of the disadvantages of hydrotransport is the high erosion rates since the oil sand is very abrasive. Bukharin et al [65,66] suggested replacing hydrotransport with cavitation jet vessels. It was shown that cavitating jets produced typical cavitation erosion on aluminum plates and had an ability to separate bitumen from oil sand.…”
Section: Bitumen Separation Using Cavitating Jetsmentioning
confidence: 99%
“…In ref , a fundamentally new approach to bitumen extraction based on utilization of a cavitating jet has been suggested and investigated. It has been shown that the bitumen extraction in the first step of the overall process mentioned above can be achieved at room temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the suggested approach did not require long pipelines. The experimental results obtained in refs and were based on testing oil sands samples having the same mass (100 g) in the same volumetric environment. Thus, the solids density in the slurry remained the same at the beginning of each test.…”
Section: Introductionmentioning
confidence: 99%